Characteristics of Hypertension Patients at Wolasi Community Health - Asdwiyenti Miftahulresty Aksi; Ayuningtyas Mardhatillah; Imran Imran (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background:Hypertension is a non-communicable disease and a leading cause of morbidity and mortality in Indonesia. Various factors, such as age, gender, and weight, can influence this condition. Although often associated with obesity, hypertension is also common in people of normal weight. Objective:This study aims to understand the characteristics of hypertension patients based on gender, age and body weight at Wolasi Community Health Center in 2025. Method:This study employed a descriptive design with a quantitative approach. The population of this study included all hypertension patients registered at the Wolasi Community Health Center between January and September 2025, totaling 228 individuals, all of whom were sampled. Secondary data were obtained from the Community Health Center's annual report. Analysis was conducted descriptively using frequency distributions and percentages. Results:Research findings indicate that the majority of hypertension patients are women (77%), with the largest age group being 56–65 years (29%), and the normal weight category (44%). Based on blood pressure classification, the majority of respondents were placed in the stage 1 hypertension category (43.28%), followed by stage 2 hypertension (22.82%) and prehypertension (21.96%). Conclusion:Incidences of hypertension at the Wolasi Community Health Center in 2025 were more common in older women of normal weight. This indicates that hypertension not only affects obese individuals but can also occur in those of normal weight due to other factors such as age, hormonal changes, and visceral fat distribution. Preventive measures through education, regular blood pressure checks, and lifestyle changes are crucial for all age and weight groups. Keywords: Humans,Famale,Male,Aged,Blood Pressure